2021
DOI: 10.3389/fonc.2021.694331
|View full text |Cite
|
Sign up to set email alerts
|

Intratumor Heterogeneity of MIF Expression Correlates With Extramedullary Involvement of Multiple Myeloma

Abstract: Macrophage migration inhibitory factor (MIF) has been shown to promote disease progression in many malignancies, including multiple myeloma (MM). We previously reported that MIF regulates MM bone marrow homing and knockdown of MIF favors the extramedullary myeloma formation in mice. Here, based on MIF immunostaining of myeloma cells in paired intramedullary and extramedullary biopsies from 17 patients, we found lower MIF intensity in extramedullary MM (EMM) versus intramedullary MM (IMM). Flow cytometry and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…MIF has been shown to directly promote disease progression in many malignancies, including MM. [ 42 43 44 ] MIF also reshaped the macrophage phenotype to an immunosuppressed status, which promotes disease progression in MM. [ 45 ] Templin et al [ 46 ] have noted that IL16 promotes the malignant phenotype of myeloma cells through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…MIF has been shown to directly promote disease progression in many malignancies, including MM. [ 42 43 44 ] MIF also reshaped the macrophage phenotype to an immunosuppressed status, which promotes disease progression in MM. [ 45 ] Templin et al [ 46 ] have noted that IL16 promotes the malignant phenotype of myeloma cells through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that APRIL expressed by monocytes/macrophages is a ligand of BCMA expressed by multiple myeloma cells, which can rescue interleukin 6 (IL-6)–dependent MM cell lines from apoptosis following IL-6 deprivation, stimulate MM cell growth via cyclin D-dependent G1/S cell cycle progression and induced immunosuppression in the bone marrow microenvironment [ 75 79 ]. Macrophage migration inhibitory factor (MIF) has been shown to promote disease progression directly in many malignancies, including multiple myeloma (MM) [ 80 82 ]. MIF also reshaped the macrophage phenotype to immunosuppressed status, which then promotes disease progression in MM [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…MIF (Macrophage Migration Inhibitory Factor) has been shown to accelerates the development of the disease in multiple myeloma. MM patients with high MIF had a worse prognosis (Wang et al, 2020;Xu et al, 2021). A number of studies have shown that PLA2G4A (placental phospholipase A24A is involved in the biological procedure of stress response in various diseases (Brien et al, 2017;Zhang et al, 2018;Mishra et al, 2022).…”
Section: Discussionmentioning
confidence: 99%